2016
DOI: 10.1007/s12282-016-0677-4
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel, cyclophosphamide, and trastuzumab as neoadjuvant chemotherapy for HER2-positive primary breast cancer

Abstract: Four cycles of HER-TC may be a NAC option for HER2-positive breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Considering that only a small proportion of patients with Her2-positive status were treated with trastuzumab in the neoadjuvant setting, the pCR rate of Her2-positive patients in our study was not so high as in studies with trastuzumab-based NAC. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Considering that only a small proportion of patients with Her2-positive status were treated with trastuzumab in the neoadjuvant setting, the pCR rate of Her2-positive patients in our study was not so high as in studies with trastuzumab-based NAC. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The objective of our study was to evaluate the efficacy of prophylactic anti-allergic drug administration against TC-related skin eruption in patients with primary breast cancer. This study is a subanalysis of data that we previously reported as part of a combined phase 2 study of TC NAC and HER-TC NAC [3,4]. This study was an openlabel, nonrandomized study, which was conducted at seven different institutions.…”
Section: Methodsmentioning
confidence: 99%
“…The cumulative incidence of skin eruption every chemotherapy cycle is summarized in Figure 3. As shown in Figure 3, the onset of skin efficacy and tolerability of TC neoadjuvant chemotherapy (NAC) and HER-TC NAC in patients with breast cancer in previous studies [3,4]. Therefore, in this work, we re-analyzed the data from those studies to retrospectively evaluate the prophylactic effectiveness of anti-allergic drugs against TC/HER-TC-related skin eruption among the patients in our clinical trial.…”
Section: Skin Toxicitiesmentioning
confidence: 99%
“…[5][6][7] A combination of docetaxel and cyclophosphamide are used as neoadjuvant chemotherapy in HER2-negative primary breast cancer and a combination of docetaxel, cyclophosphamide, and trastuzumab as neoadjuvant chemotherapy for HER2-positive primary breast cancer. 8,9 In most cases, cyclophosphamide may damage the immune function of cancer patients, and this may lead to invasive fungal infections (IFIs). Besides, chemotherapy regimens that include cyclophosphamide have a >20% incidence of febrile neutropenia, and this will put patients at higher risk of developing IFIs.…”
Section: Introductionmentioning
confidence: 99%